Women in business: Chicken and seed dissemination in Ethiopia and Tanzania - International Livestock Research Institute (International Livestock Research Institute, 2022)
The ‘Women in Business: Chicken Dissemination Project (WiB)’ was implemented by the International Livestock Research Institute (ILRI) in collaboration with partners in Tanzania and Ethiopia. The three-year project developed, promoted and tested women-led chicken businesses in the two countries to empower women and young graduates and improved the food and nutrition security of their households.